Haematopinus Infestations and Mycoplasma Infections of Water Buffalo (Bubalus bubalis) Herds in National Parks of Hungary - Egri, B.; Stipkovits, L.; Piszmán, R. (Journal of Buffalo Science, 2016)
The biology, epidemiology and pathology of sucking louse infestation and Mycoplasma infection of water buffalo (Bubalus bubalis) herds in Hungarian national parks were studied between 19 December 2011 and 4 May 2012. A total of 333 water buffaloes were examined in buffalo stocks of the Balaton Uplands, Fertő-Hanság and Kiskunság National Parks. The objective was to determine the prevalence and rate of sucking louse infestation and mycoplasma infection among water buffaloes. Always an area of identical size (2 cm2) was examined on the right or left side of the middle part of the animals’ neck. A total of 3106 eggs, 10 nymphs and 105 adults of the sucking louse Haematopinus tuberculatus were identified with the help of a Conrad USB microscopic camera and a Wild-Leitz-Leica M420 photomacroscope. The data were evaluated using the Quantitative Parasitology software QP 3.0. The prevalence of mycoplasmas was determined in 20 randomly selected buffaloes of two national parks with the help of sterile nasal and vaginal transport swabs (Sarstedt). All of the 10 nasal swabs collected from buffaloes in the Balaton Uplands National Park contained Mycoplasma bovirhinis and three swab samples yielded M. bovis as well. Mycoplasma bovirhinis was cultured from 8 out of 10 swabs taken from the vagina, and three vaginal samples also yielded M. bovis. Similar results were obtained by testing samples collected from buffaloes in the Kiskunság National Park (Mórahalom). All ten nasal swab samples yielded M. bovirhinis. From two samples a mixture of M. bovirhinis and M. bovis was cultured. Nine out of the 10 vaginal swabs yielded M. bovirhinis while two showed a combined infection by M. bovis and M. bovirhinis.